Neural innovations and the diversification of African weakly electric fishes - Carlson, Bruce A. (Landes Bioscience, 2011)
In African mormyrid fishes, evolutionary change in a sensory region of the brain established an ability to detect subtle variation in electric communication signals. In one lineage, this newfound perceptual ability triggered a dramatic increase in the rates of signal evolution and species diversification. This particular neural innovation is just one in a series of nested evolutionary novelties that characterize the sensory and motor systems of mormyrids, the most speciose group of extant osteoglossomorph fishes. Here we discuss the behavioral significance of these neural innovations, relate them to differences in extant species diversity, and outline possible scenarios by which some of these traits may have fueled diversification. We propose that sensory and motor capabilities limit the extent to which signals evolve and, by extension, the role of communication behavior in the process of speciation. By expanding these capabilities, neural innovations increase the potential for signal evolution and species diversification.